A Rare Case of Pyoderma Gangrenosum in a HIV Positive Patient - Loganathan, Eswari; Banu, Asima (Asian Journal of Medical Sciences, 2011)
HIV infection can lead to varied spectrum of associated disease conditions. Pyoderma gangrenosum is a neutrophilic dermatosis that may be associated with myeloid malignancies. Less information is available about the association of pyoderma gangrenosum with lymphoid malignancies. We report a rare case of pyoderma gangrenosum in association with Non hodgkins lymphoma(NHL) of diffuse large B cell type. In this case the lesion which showed NHL features occurred in the perianal region, coexisting with pyoderma gangrenosum lesions in the perianal, lower limb and abdominal region. Another interesting feature is the occurrence of both these conditions in a HIV-positive patient with severe immunologic failure to first line antiretroviral therapy contributing to the refractoriness to treatment. Key Words: HIV; pyoderma gangrenosum; Non Hodgkins Lymphoma DOI: http://dx.doi.org/10.3126/ajms.v2i2.4029 Asian Journal of Medical Sciences 2 (2011) 128-130